2014
DOI: 10.1136/archdischild-2014-307384.1223
|View full text |Cite
|
Sign up to set email alerts
|

PO-0581 Nutrition During Therapeutic Hypothermia In Neonates

Abstract: Adequate nutrition during therapeutic cooling for ischaemic injury in the newborn is important in minimising long-term neurological morbidity.1 National TOBY guidelines suggest enteral feeds may be ‘cautiously introduced’ during cooling following the correction of biochemical and metabolic disturbances.2 However, it has been suggested that neonates exposed to hypoxic injury are at increased risk of developing necrotizing enterocolitis (NEC) and so feeds should be withheld until re-warming.3 A national surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…Furthermore, and in contrast to surveys of UK practice that suggest that enteral feeding is becoming more common during hypothermia (i.e. 29% of units in 2010 6 vs. 59% of units in 2016 3 ), we found that the proportion of babies for whom enteral feeds were introduced (31%) remained stable over the 8-year period 2010-17. These findings may be explained by incomplete survey coverage or simply reflect the difference between reported and actual practice.…”
Section: Results In Contextcontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, and in contrast to surveys of UK practice that suggest that enteral feeding is becoming more common during hypothermia (i.e. 29% of units in 2010 6 vs. 59% of units in 2016 3 ), we found that the proportion of babies for whom enteral feeds were introduced (31%) remained stable over the 8-year period 2010-17. These findings may be explained by incomplete survey coverage or simply reflect the difference between reported and actual practice.…”
Section: Results In Contextcontrasting
confidence: 99%
“…For comparison, the most recent Cochrane review 2 in this area identified 11 trials and 1505 infants in total. NEC is one of the most feared complications of neonatal care 6 and is well described in case studies and single-centre series in babies with HIE. 37,38 There has been a paucity of robust incidence data because studies have hitherto been limited by small size and the use of subjective definitions of NEC.…”
Section: Results In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Our survey illustrates widespread variability in the use of enteral and parenteral nutrition in these infants. As compared with the survey published as an abstract in 2014, 17 a significantly higher proportion of units started enteral feeds during TH. Given there are 69 NICUs that offer active TH and Allen et al had contacted only 47 units, our response rate of 71% was satisfactory compared with their rate of 89%.…”
Section: Discussionmentioning
confidence: 73%
“…16 A survey presented in 2014 reported that 21% of UK neonatal units offered trophic feeds during TH, but lacked data on when milk was introduced, milk type, volumes, frequency and advancement of feeds. 17 Given reports of the safety of small-volume enteral feeds during TH, 18 we hypothesised that rates of enteral feeding would have increased. In this study, we aimed to survey clinicians in UK neonatal units providing active TH for determining current nutritional practices during and after TH in infants with HIE.…”
Section: Introductionmentioning
confidence: 99%